2016
DOI: 10.1016/j.ensci.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

MELAS and Kearns–Sayre overlap syndrome due to the mtDNA m. A3243G mutation and large-scale mtDNA deletions

Abstract: This paper reported an unusual manifestation of a 19-year-old Chinese male patient presented with a complex phenotype of mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes (MELAS) syndrome and Kearns–Sayre syndrome (KSS). He was admitted to our hospital with the chief complaint of “acute fever, headache and slow reaction for 21 days”. He was initially misdiagnosed as “viral encephalitis”. This Chinese man with significant past medical history of intolerating fatigue presented paroxysmal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Leukoencephalopathy in KSS was also demonstrated by MRI to show cerebral, cerebellar and brainstem atrophy. T2 signals include subcortical prolongation with subcortical calcifications, with or without bilateral basal ganglia calcific deposits [ 39 , 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leukoencephalopathy in KSS was also demonstrated by MRI to show cerebral, cerebellar and brainstem atrophy. T2 signals include subcortical prolongation with subcortical calcifications, with or without bilateral basal ganglia calcific deposits [ 39 , 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The features of various neurometabolic disorders characterized by the occurrence of SLEs include genetic and molecular basis, clinical manifestations, MRI and EEG results, onset and prevalence and treatment methods ( Table 1 ) [ 2 , 3 , 4 , 7 , 8 , 9 , 11 , 13 , 14 , 15 , 16 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , …”
Section: Resultsmentioning
confidence: 99%
“… 42 This mutation also led to mitochondrial encephalomyopathy, lactic acidosis and stroke-like symptoms (MELAS). 43 Molecular analysis revealed that this mutation reduced the steady-state level, aminoacylation, as well as codon recognition of tRNA Leu(UUR) . 44 As a result, the A3243G mutation caused the pre-termination of transcription and expression impeding of normal rRNA, thus compromising mitochondrial protein synthesis, ATP synthesis and organic metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, because a variety of genetic mutations deleteriously affect mitochondrial function it can be very daunting to make a comprehensive diagnosis (Gorman et al, 2015). The clinical presentations of mitochondrial disorders have common overlaps between Mitochondrial Encephalomyopathy, Lactic Acidosis and Stroke-like episodes syndrome (MELAS) and KSS (Yu, et al, 2016). Mitochondrial encephalomyopathy is defined by disease, damage, or malfunction of the brain indicating that KSS patients have a severely affected central nervous system (CNS) (Quijada-Fraile et al, 2014).…”
Section: Introductionmentioning
confidence: 99%